Revision of a unique Australian leafhopper genus Stenopsoides Evans (Hemiptera: Cicadellidae: Idiocerinae: Macropsini) - Semeraro, Linda; Fletcher, Murray J.; Malipatil, Mallik B.; Constant, Jerome; New, Timothy R. (Zootaxa, 2021)
The Australian genus Stenopsoides Evans (Idiocerinae: Macropsini) is revised. The type species, S. turneri Evans, is redescribed and three new species are added: S. newi Semeraro sp. nov., S. punctatus Semeraro sp. nov. and S. truncatus Semeraro sp. nov.. Species photographic plates, a distribution map and an illustrated key to the four species are provided. The possibility of parthenogenetic reproduction occuring in this genus is discussed.